2017
DOI: 10.1002/chem.201703526
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Quaternary Δ4‐ and Δ5‐Dehydroprolines Based on a Two‐Step Formal [3+2] Cycloaddition of α‐Aryl and α‐Alkyl Isocyano(thio)acetates with Vinyl Ketones

Abstract: A divergent synthesis of optically active quaternary Δ - and Δ -dehydro prolines is developed based on the first catalytic enantioselective conjugate addition of α-substituted isocyano(thio)acetates to vinyl ketones that is general for both α-aryl and α-alkyl isocyano(thio)acetates. The new tetrasubstituted C-N stereocenter is formed without the need of any metal salt due to a bifunctional tertiary amine/squaramide catalyst, featuring a bulky polyaryl sidearm and an unusually short squaramide diamide H⋅⋅⋅H int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…In 2017, the Palomo group utilized a bifunctional tertiary amine/squaramide catalyst 17 g bearing a bulky polyaryl sidearm to realize an efficient asymmetric conjugate addition of α‐substituted isocyano(thio)acetates 1 to simple vinyl ketones 101 [71] . As shown in Scheme 23, the corresponding products 102 featuring a quaternary carbon stereocenter were isolated with yields within 30–96 % and ee values up to 99 % (Scheme 23 a).…”
Section: Michael Addition Reactions Of Isocyanides With Electron‐defimentioning
confidence: 99%
“…In 2017, the Palomo group utilized a bifunctional tertiary amine/squaramide catalyst 17 g bearing a bulky polyaryl sidearm to realize an efficient asymmetric conjugate addition of α‐substituted isocyano(thio)acetates 1 to simple vinyl ketones 101 [71] . As shown in Scheme 23, the corresponding products 102 featuring a quaternary carbon stereocenter were isolated with yields within 30–96 % and ee values up to 99 % (Scheme 23 a).…”
Section: Michael Addition Reactions Of Isocyanides With Electron‐defimentioning
confidence: 99%
“…Incidentally, the sulfonyl group in the adducts would be susceptible to several ulterior transformations, including reductive removal . To our delight, as the results in Scheme show, α‐branched ketones 4 reacted with 6 in the presence of C7 , C8 , or C9 (formulas in Table ) to afford adducts 7 – 9 from reaction exclusively at the α site, albeit in variable yields and with different enantioselectivities. For example, the reaction between methyl ketone 4 a and 6 in the presence of C9 reached 81 % conversion after 16 h at room temperature, and product 7 was obtained with 79 % ee .…”
Section: Resultsmentioning
confidence: 99%
“…Reactions of cyclic ketones 10-20 and 22-26 with 1,1-bis(phenylsulfonyl)ethylene (6): General procedure:C atalyst C8 (10 mol %) or C9 (5 mol %) was added to as olution of the corresponding cyclic a-alkenyl ketone (0.15 mmol) and 1,1-bis(phenylsulfonyl)ethylene (69 mg, 0.23 mmol) in CH 2 Cl 2 at 0 8C( ketones 10-20)o rr oom temperature (ketones [22][23][24][25][26]. The resulting solution was stirred until the reaction was complete (typically 16 h), as monitored by TLC (hexane/EtOAc,80:20).…”
Section: Methodsmentioning
confidence: 99%
“…With the N‐benzyl analog C3 diastereoselectivity was improved at the expense of enantioselectivity (80 % ee , entry 2), whereas the related cyclohexyldiamine‐derived squaramide catalyst C4 afforded product 5A a with high ee , but yet suboptimal diastereoselectivity ( dr 4:1, 92 % ee , entry 3; dr =diastereomeric ratio). After additional screening that showed thiourea catalysts inferior in reactivity and selectivity (e.g., C5 , entry 4), we finally found that the reaction in the presence of newly developed catalyst C6 afforded the desired product 5A a in 82 % yield, a remarkable 19:1 dr and 94 % ee (entry 5). Although the superior behavior of catalyst C6 correlates well with previous observations, it seems that its origin cannot be explained by steric congestion merely as the bulky neopentyl‐derived catalyst C 7 was comparatively inferior (entry 6).…”
Section: Resultsmentioning
confidence: 99%
“…After additional screening that showed thiourea catalysts inferior in reactivity and selectivity (e.g., C5 , entry 4), we finally found that the reaction in the presence of newly developed catalyst C6 afforded the desired product 5A a in 82 % yield, a remarkable 19:1 dr and 94 % ee (entry 5). Although the superior behavior of catalyst C6 correlates well with previous observations, it seems that its origin cannot be explained by steric congestion merely as the bulky neopentyl‐derived catalyst C 7 was comparatively inferior (entry 6).…”
Section: Resultsmentioning
confidence: 99%